A scoping review of stroke rehabilitation in Africa: interventions, barriers, and research gaps - Nicholas Aderinto; Gbolahan Olatunji; Emmanuel Kokori; Chinonyelum Emmanuel Agbo; Adetola Emmanuel Babalola; Ismaila Ajayi Yusuf; Edun Mariam Tolulope; Anuoluwa Oyeboyin Oyelude; Faith Adedayo Adejumo; Israel Charles Abraham (Journal of Health, Population and Nutrition)
Abstract Stroke is a leading cause of disability worldwide, with low- and middle-income countries (LMICs), particularly in Africa, experiencing an increasing burden due to rising incidences driven by urbanization, lifestyle changes, and non-communicable diseases. This scoping review maps stroke rehabilitation interventions in Africa, identifying barriers to implementation and adherence, and highlighting research gaps to inform future policy and clinical practices. A literature search was conducted across PubMed, Scopus, Web of Science, Embase, and African Journals Online (AJOL), supplemented by grey literature from WHO reports and government publications. Inclusion criteria focused on studies of stroke rehabilitation interventions in African countries, targeting adults diagnosed with stroke, and included randomized controlled trials, cohort studies, qualitative studies, and systematic reviews. Findings indicate that stroke rehabilitation interventions in Africa, including physical therapy, task-specific training, psychoeducational programs, tele-rehabilitation, mobile phone-supported interventions, and programs targeting activities of daily living (ADLs), are implemented in some settings to enhance functional independence, motor, cognitive, and speech functions, and psychological well-being. However, adherence to these protocols is often limited by significant barriers, including financial constraints, geographical and transportation challenges, a shortage of skilled rehabilitation professionals, cultural and language barriers, and patient-related factors such as cognitive impairments and lack of social support. The review also reveals variability in the availability of standardized rehabilitation protocols across African settings, with some regions lacking consistent implementation. Research gaps include insufficient epidemiological data, limited evaluation of cost-effective and culturally appropriate rehabilitation models, and underexplored caregiver burden. This review advocates further studies on technology integration, community-based rehabilitation, and culturally tailored interventions to improve adherence and accessibility. It also emphasizes addressing systemic and infrastructural barriers to ensure equitable access to rehabilitation services for stroke survivors across Africa. Future research should focus on optimizing rehabilitation strategies, reducing long-term disability, and improving quality of life for stroke survivors in Africa.